The Effect of Contextual Factors on Health Information–Seeking Behavior of Isfahan Diabetic Patients. Issue 1 (2nd January 2016) - Zare-Farashbandi, Firoozeh; Lalazaryan, Anasik; Rahimi, Alireza; Hasssanzadeh, Akbar
ABSTRACT: The aim of this study was to examine the effect of contextual factors on the health information–seeking behavior of diabetic patients in Isfahan. This is an applied study using the survey method. Three hundred sixty-two patients were selected using stratified random sampling. Longo's information-seeking behavior questionnaire was used to collect data and SPSS 20 software was used to analyze data. Pearson correlation index showed that by controlling age, there was a direct relation between longevity of diagnosis and some information-seeking factors ( P < .05, r > 0). One-way analysis of variance (ANOVA) test showed that the average score of some factors of diabetic patient's information-seeking behavior during pregnancy are significantly higher than patients with prediabetes and diabetes ( P < .05). Independent t test showed a statistically significant difference between information-seeking behavior of patients with a family history of diabetes and patients without a family history of diabetes ( P < .05). Therefore, due to the importance of health care in diabetic pregnant women and prediabetic patients, necessary steps need to be taken to provide these patients with suitable information sources. Also, investigating the factors affecting health information–seeking behavior of patients with chronic disease will help understand and satisfy their information needs, leading to the improvement of the patients' self-care and prevent complications.